Announcement of public relations in Iraqi press (Journal of the College of Basic Education, 2022)
The public relations advertisement aims to strengthen the connection with society, and in order to achieve this, itIt works to highlight the bright image of the institution in the community, as a communication method that serves the community and works onthe maintenance of his interests, and on the other hand, the institution works to enhance this image through its useThis type of advertisement is used to improve its image and highlight its services. Because this type of advertisement hasIt appeared widely in newspapers, especially Al-Sabah newspaper, and there was a need for a serious study about it.